The nature and function of syntactic categories - Borsley, Robert D. (San Diego, CA : Academic Press, 2000)
To paraphrase, of the making of syntactic categories there is no end. For any theory of syntax, questions arise about its classificatory scheme: what are the categories? What properties do they have? How do they relate to each other? Eleven essays address these questions by inquiring whether there is a clear distinction between lexical and functional categories, how syntactic categories relate to semantic categories, the relation between syntactic and morphological information, as well as other inquiries. Above all the essays highlight the centrality of questions about syntactic categories for a number of different theoretical frameworks. It discusses a broad range of questions about syntactic categories and presents a number of theoretical frameworks.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Grammar, Comparative and general -- Syntax; Grammar, Comparative and general -- Grammatical categories; Grammar, syntax; Semantics; Language Arts & Disciplines -- Grammar & Punctuation; Language Arts & Disciplines -- Linguistics -- General